Diversity of the genus Cryobacterium and proposal of 19 novel species isolated from glaciers - Liu, Qing; Yang, Lei-Lei; Xin, Yu-Hua (Frontiers in Microbiology, 2023)
The genus Cryobacterium is a bacterial group specific to cryospheric environments, which, at present, includes 14 species. In this study, we analyzed 101 genomes of Cryobacterium with pure cultures obtained from Genbank. They could be classified into 44 species based on average nucleotide identity (ANI) analysis, showing the diversity of Cryobacterium. Among these, 19 strains in our laboratory were isolated from the glacier samples in China. The pairwise ANI values of these 19 strains and known species were less than 95%, indicating that they represented 19 novel species. The comparative genomic analysis showed significant differences in gene content between the two groups with maximum growth temperature (Tmax) ≤20°C and Tmax >20°C. A comprehensive and robust phylogenetic tree, including 14 known species and 19 novel species, was constructed and showed five phylogenetic branches based on 265 concatenated single-copy gene sequences. The Tmax parameter had a strong phylogenetic signal, indicating that the temperature adaptation of Cryobacterium was largely through vertical transfer rather than from horizontal gene transfer and was affected by selection. Further, using polyphasic taxonomy combined with phylogenomic analysis, we proposed 19 novel species of the genus Cryobacterium by the following 19 names: Cryobacterium serini sp. nov., C. lactosi sp. nov., C. gelidum sp. nov., C. suzukii sp. nov., C. fucosi sp. nov., C. frigoriphilum sp. nov., C. cryoconiti sp. nov., C. lyxosi sp. nov., C. sinapicolor sp. nov., C. sandaracinum sp. nov., C. cheniae sp. nov., C. shii sp. nov., C. glucosi sp. nov., C. algoritolerans sp. nov., C. mannosilyticum sp. nov., C. adonitolivorans sp. nov., C. algoricola sp. nov., C. tagatosivorans sp. nov., and C. glaciale sp. nov. Overall, the taxonomy and genomic analysis can improve our knowledge of phenotypic diversity, genetic diversity, and evolutionary characteristics of Cryobacterium.